El régimen jurídico de la acuicultura en el Perú - Ramos Huaytalla, Bruno; García Castillo, Rolando (Pontificia Universidad Católica del Perú, 2022)
Aquaculture is an economic activity regulated by Peruvian law, the purpose of which is to cultivate aquatic species and ensure the conservation of biodiversity. In this article, the authors start by analyzing the current regulations on hydrobiological resources and then identify the regulation of aquaculture activity, as well as the administrative sanctioning procedure applicable to non-compliance with aquaculture, environmental and sanitary obligations derived from that activity.

La acuicultura es una actividad económica regulada en la legislación peruana, cuyo objeto es realizar el cultivo de especies acuáticas y garantizar la conservación de la biodiversidad. En este artículo, los autores parten de analizar la normativa vigente sobre los recursos hidrobiológicos para luego identificar la regulación de la actividad acuícola, así como el procedimiento administrativo sancionador aplicable ante el incumplimiento de las obligaciones de índole acuícola, ambiental y sanitaria derivadas de aquella actividad.
The legal regime of aquaculture in Peru
Keywords: General Aquaculture Law; Aquaculture activities; Aquaculture of limited resources; Aquaculture of micro and small enterprises; Aquaculture of medium; Large enterprises; Ley general de acuicultura; Actividades acuícolas; Acuicultura de recursos limitados; Acuicultura de micro y pequeña empresa; Acuicultura de mediana; Gran empresa; https://purl.org/pe-repo/ocde/ford#5.05.01